Constraining Star Formation in M87 Using Deep Hubble Space Telescope UV Data - Prathamesh Tamhane; William Waldron; Ming Sun; Silvia Martocchia; Claudia Maraston; Alessandro Boselli; William Forman; Massimo Gaspari; Juhi Tiwari; Megan Donahue; G. Mark Voit; Tim Edge; et al. (The Astrophysical Journal)
We analyzed the deepest Hubble Space Telescope F275W ultraviolet (UV) imaging of M87 to obtain the most robust constraints on its star formation rate (SFR) and star formation history (SFH). After removing the galaxy continuum and globular clusters, we detected an excess of UV point sources near the center. By comparing their colors to young stellar source (YSS) colors generated by stochastically simulated star formation (SF) for various SFRs and SFHs, we ruled out their origin as a UV-upturn population and identified them as YSS. We found an extremely low SFR of ∼2 × 10 ^−5 M _⊙ yr ^−1 in M87, with evidence of a weak starburst ∼125 Myr ago that formed ∼1000 M _⊙ of stars. Unlike other cool-core clusters where SF is stronger and directly linked to cooling gas, we found no spatial correlation between YSS and H α filaments. Comparing SF activity with M87’s active galactic nucleus (AGN) outburst history suggests that recent AGN feedback events (≲12 Myr ago) neither triggered nor were associated with any detectable SF; however, earlier outbursts may have triggered weak starbursts. We detected UV filaments cospatial with H α filaments with similar lengths and widths, though they are obscured by dust near the center. These filaments are likely powered by metal-line emission from collisional ionization, suggesting ongoing low-level precipitation of the intracluster medium. Our results indicate that AGN feedback has quenched SF significantly in M87 for at least 200 Myr, even though some precipitation persists. Additionally, we identified a hotspot created by the counterjet, with the spectral index also constrained.